Automated teller machine using UMP smart card in DB2 - Wong, Kam Man (2012)
This document discusses about Automated Teller Machine using UMP smart card in DB2.In UMP,students,lecturer,or staff might bring more than one smart card with them and thus there is always make inconvenient for them.This project is developed to use an all-in-one smart card that can perform banking transaction and perform as student ID card or staff ID card as well.The proposed system will have two part, user interface and database.The database is installed in z/OS environment while the user interface is in Windows.To develop this proposed system,System Development Life Cycle (SDLC) has been chosen as methodology.